Microplastic Intake, Its Biotic Drivers, and Hydrophobic Organic Contaminant Levels in the Baltic Herring - Ogonowski, Martin; Wenman, Viktoria; Barth, Andreas; Hamacher-Barth, Evelyne; Danielsson, Sara; Gorokhova, Elena (Frontiers in Environmental Science, 2019)
It is commonly accepted that microplastic (MP) ingestion can lead to lower food intake and bioaccumulation of hydrophobic organic contaminants (HOCs) in aquatic organisms. However, causal links between MP and contaminant levels in biota are poorly understood and in situ data are very limited. Here, we investigated whether HOC concentrations in herring muscle tissue (Clupea harengus membras) are related to MP ingestion using fish caught along the West coast of the Baltic Sea. The MP occurrence exhibited a large geographic variability, with MP found in 22.3% of the fish examined, and the population average being 0.9 MP ind-1. However, when only individuals containing MP were considered, the average MP burden was 3.9 MP ind-1. We also found that MP burden decreased with reproductive stage of the fish but increased with its body size. To predict MP abundance in fish guts, we constructed a mass-balance model using literature data on MP in the water column and physiological rates on ingestion and gut evacuation for clupeids of a similar size. The model output was in agreement with the observed values, thus supporting the validity of the results. Contaminant concentrations in the muscle tissue varied substantially across the study area but were unrelated to the MP levels in fish, suggesting a lack of direct links between the levels of HOCs and MP ingestion. Thus, despite their ubiquity, MP are unlikely to have a measurable impact on food intake or the total body burden of hydrophobic contaminants in Baltic herring.